Systematics of hairy armadillos and the taxonomic status of the Andean hairy armadillo (Chaetophractus nationi) - Abba, Agustín Manuel (2015)
Hairy armadillos constitute an ecologically homogeneous and morphologically similar group with currently 5 species classified in the subfamily Euphractinae. Among them, the Andean hairy armadillo Chaetophractus nationi (Xenarthra, Cingulata, Dasypodidae) is a small, endangered armadillo that has long been suspected to represent a high-altitude variant of Chaetophractus vellerosus. Here, we report the 1st phylogenetic systematics assessment of hairy armadillos using morphological and molecular analyses of all described species with focus on the status of the Andean hairy armadillo. Multivariate analyses of shape variation based on 3-dimensional landmark coordinates of skulls allowed a clear differentiation of each species with the exception of C. vellerosus and C. nationi, within which only a latitudinal and/or altitudinal gradient in size was apparent. Moreover, analyses of mitochondrial DNA control region (D-loop) revealed a single C. nationi haplotype that appeared to be identical with a C. vellerosus haplotype from Argentina. Identical sequences in C. vellerosus and C. nationi were also observed for 3 of the 5 non-coding nuclear markers investigated. Based on these data, we propose that C. nationi should be considered as a synonym of C. vellerosus. However, this taxonomic change should not preclude the protection of the high-altitude Bolivian populations that are steadily declining because of their overexploitation for traditional purposes. Finally, phylogenetic analyses of euphractine armadillos based on a combination of 6 non-coding nuclear markers and 2 nuclear exons suggest the paraphyly of the genus Chaetophractus, with C. vellerosus being more closely related to Zaedyus pichiy than to C. villosus.